FACTORS AFFECTING ENTREPRENEURIAL READINESS AS AN EFFORT TO REDUCE THE UNEMPLOYMENT RATE (SYSTEMATIC LITERATURE REVIEW) - Choirunnisa, Salsabila Safitri; Lestari, Ana Dwi Setyo; Pudjiastuti, Fransisca Ucik; Wardana, Ludi Wishnu; Narmaditya, Bagus Shandy (Nusantara Economics and Entrepreneurships Journals, 2024)
The purpose of this study is to analyze the factors that influence entrepreneurial readiness as an effort to reduce the unemployment rate. The problem faced is the low intention and readiness of the younger generation to engage in entrepreneurial activity, which is influenced by individual attitudes. The research method used is a systematic analysis of literature to identify key findings related to entrepreneurial readiness, attitudes, mindset, and entrepreneurial interest. The results showed that personal, social, and economic factors influence individual interest in entrepreneurship. Collaboration between educational institutions and industry is considered important in shaping young people's entrepreneurial readiness. This study provides insights into the complexity of factors influencing entrepreneurial readiness and their relevance in facing the challenges of the global economy